Pengaruh Sanksi Disiplin Kerja terhadap Promosi Jabatan Melalui Kinerja Pegawai sebagai Variabel Mediasi: (Studi pada Pegawai Kecamatan Kangayan Kabupaten Sumenep) - Hamka Hamka; Hadi Susanto; Sri Mulyani (Universitas 45 Surabaya, 2025)
Hamka, 2025. The Influence of Work Discipline Sanctions on Job Promotion Through Employee Performance as a Mediating Variable (Study on Employees of Kangayan District, Sumenep Regency) Study on Employees . Postgraduate Program, Wijaya Putra University, Surabaya. Based on its approach, this research is included in the explanatory research type . The research sample was 41 respondents. The objectives of this research are 1) To test and analyze the significant impact of sanctions discipline work towards promotion position Kangayan District Regency Sumenep. 2) To test and analyze the significant influence of sanctions discipline work on performance Kangayan District employee Regency Sumenep. 3) To test and analyze the significant influence of performance employee towards promotion position Kangayan District Regency Sumenep. 4) To test and analyze the significant influence of work disciplinary sanctions on promotions. Position Kangayan District, Sumenep Regency, which is mediated by employee performance. The research results show that: 1) sanctions discipline Work influential positive significant towards promotion position Kangayan District Regency Sumenep with mark original sample of 0.251. 2) sanctions discipline Work influential positive significant to performance Kangayan District employee Regency Sumenep with mark original sample of 0.526. 3) performance employee influential positive significant to promotion position Kangayan District Regency Sumenep with mark original sample of 0.335. 4) work disciplinary sanctions have an effect positive No significant to promotion position Kangayan District, Sumenep Regency, which is mediated by employee performance with mark original sample of 0.176.